Influence of Digestion Procedure and Residual Carbon on Manganese, Copper, and Zinc Determination in Herbal Matrices by Atomic Absorption Spectrometry - Dorota Adamczyk-Szabela; Piotr Anielak; Wojciech M. Wolf (Journal of Analytical Methods in Chemistry)
Mineralization to the complete oxidation of sample carbon component does not always assure the best analyte recovery. Particular attention should be paid to the presence of silicon in the investigated plant sample and especially in the certified reference material for which Si content is scarcely given by the providers. During mineralization without addition of the hydrofluoric acid, the residual carbon may block silica surfaces and increase availability of an analyte for its spectral determination in the solution. This issue is of particular relevance because standard protocols for digestion of plant matrices often do not support hydrofluoric acid addition. Several procedures recommended for decomposition of herbal plants were applied for the respective certified reference material and examined in detail. Manganese, copper, and zinc contents were analyzed in all samples by the flame atomic absorption spectrometry. Additionally, the residual carbon was determined in all mineralizates. Silicon content was analyzed by the X-ray fluorescence method. The best recoveries were observed for samples characterized by relatively high residual carbon.